PERLINDUNGAN SUMBER DAYA PERIKANAN LAUT SEBAGAI BENTUK TANGGUNG JAWAB PEMERINTAH DAERAH DI PERAIRAN LAUT WILAYAH PROVINSI ACEH - ADWANI ADWANI (Fakultas Hukum Universitas Muhammadiyah Yogyakarta, 2012)
The Article 12 Paragraph (1) of The Law of the Republic of Indonesia No. 31 of 2004 on Fisheries states that any person is prohibited from doing acts that lead to pollution and / or damage fish resources and / or the environment in fisheries management area of the Republic of Indonesia. According to the provision, the fishery resource must be protected. However, the protection given has not run properly. This study aims at explaining about the protection of marine fisheries resources in the Aceh region, the impacts of illegal fishing and the efforts to solve the problems. Library and field research was done to obtain the data of this research. The results showed that the protection done by Aceh Government is based on national regulations and local rules although there are no specific rules, the government authority of Aceh is only 12 nautical miles, the use of Rumpon and Langge can trigger conflict between fishermen, the destruction of small fish dead, and the use of trawl. The consequences are the destruction of coral reefs, the potential conflicts between fishermen, the destruction of small fish, the depletion of fish biodiversity, and the declining income of fishermen. The efforts taken are to prioritize the regulation of fisheries issues comprehensively and improve the supervision. It is recommended that local governments make special regulations in order to protect fish resources, fishermen, and enhance better coordination.